2008
DOI: 10.1097/dbp.0b013e31816d923d
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Sleep Parameters, Child Psychological Functioning, and Parenting Stress to Obesity Status Among Preadolescent Children

Abstract: These results show that the relationship of shorter sleep duration to a greater likelihood of being obese persists even after adjusting for potential confounders of child psychological/behavioral functioning and parenting stress. Gender-specific associations are similar to findings reported in samples that include adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 39 publications
(53 reference statements)
1
26
1
2
Order By: Relevance
“…The majority of studies present cross-sectional findings (N = 24) with 6 studies assessing the association between sleep duration and weight status prospectively. As can be seen in the table, the majority of studies assessed the construct of sleep duration exclusively through parent- or self-report (N = 28) 29-32,34-40,42-57 with two additional studies assessing sleep length via actigraphy. 33,41 In contrast, the majority of studies (N = 27) used measured height and weight to calculate body mass index in children with only two studies using parent- or self-report 38,46,58 , and one additional study in which it was unclear whether caretaker report or measured height and weight were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies present cross-sectional findings (N = 24) with 6 studies assessing the association between sleep duration and weight status prospectively. As can be seen in the table, the majority of studies assessed the construct of sleep duration exclusively through parent- or self-report (N = 28) 29-32,34-40,42-57 with two additional studies assessing sleep length via actigraphy. 33,41 In contrast, the majority of studies (N = 27) used measured height and weight to calculate body mass index in children with only two studies using parent- or self-report 38,46,58 , and one additional study in which it was unclear whether caretaker report or measured height and weight were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have reported no association [5, 4041], a U-shaped association [17,42], or an inverse association [4344] between sleep duration and BMI or other anthropometric measurements. Interestingly, in America, several studies reported that short sleep duration is a risk factor for obesity in children, adolescents, and adults in both cross-sectional studies and cohort studies [45–47]. A recent study in America, which included 56,507 observations in patients aged 18–85 years in the US National Health Interview Survey during 2005–2006, reported that short sleep is strongly associated with obesity after adjusting for individual characteristics, health behaviors, family environment, and census region [48].…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with stressful conditions were not entered in our study. The sample size was also different in two studies (23).…”
Section: Discussionmentioning
confidence: 99%